Molecular Detection Of Carbapenemases and ESBLs in Gram Negative Bacilli Isolated From Burn Wound Infections In Mosul City, Iraq - Ahmed Suleiman, Najla; Zeki Al-Hasso, Mahmood (Journal of Neonatal Surgery, 2025)
The presence of multidrug-resistant bacteria containing beta-lactamase enzymes (carbapenemase and Extended-Spectrum β-Lactamases ESBLs ) that cause burn wound infections is a serious threat to patient's health with the risk of their transmission to the blood stream and causing sepsis. This study seeks to identify antibiotic resistance patterns and ascertain the existence of β-lactamase enzymes (Carbapenemases and ESBLs) in Gram-negative bacilli isolated from burn wound infections. Following culture on MacConkey agar, 127 isolates were recovered from 150 samples, with Pseudomonas aeruginosa being the predominant bacterial species isolated (43.3%), succeeded by Escherichia coli (18.89%), while the isolation percentages of other species exhibited significant variability. Antimicrobial susceptibility testing results showed absolute resistance to Cefotaxime, Amoxicillin and Ceftazidime, and low resistance was against to Meropenem with rates of 58.2%. Furthermore the results showed that 0.79% of the isolates were Multiple Drug-Resistant (MDR) and 68.5% of them were Extensively Drug-Resistant (XDR), while Thirty-nine isolates (30.71%) were Pan Drug-Resistant (PDR). Phenotypic and molecular detection of carbapenemase and ESBL enzymes were performed for twenty-six antibiotic-resistant isolates, 96.2% of the isolates were ESBL producers and 80.8% were carbapenemase producers. Those results were confirmed at molecular level using 14 primers for carbapenemase genes and ESBLs (IMP, NDM, KPC, GES, NAM-C, OXA23, OXA48, OXA58, VIM, SPM, SIM, TEM, SHV, and CTX-M), results indicated the presence of carbapenemase genes OXA23, NDM, VIM with rates of 11.5% ,61.5%, 73%respectively,while OXA48 , KPC 42.3% for each. SHV, TEM and CTX-M ESBL genes detection rates were 69.2%, 84.6%, 88.4% respectively, the rest genes were not found.